2009
DOI: 10.1027/1901-2276.61.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Sense of coherence and criminal offences among young males. Findings from the Finnish from a boy to a man study

Abstract: The aim is to study associations between sense of coherence (SOC), and criminality among young males. The sample included 2314 males born 1981. Information about self-reports of SOC was obtained from obligatory military call-up. Information about criminality was obtained from the Finnish National Police Register. Self-reported poor SOC was associated with all specific crime types. Poor SOC was especially associated with high level of criminal offences.The study shows the sensitivity of the SOC-13 scale to anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Two versions of the SoC scale were created by Antonovsky, one with 29 questions (SOC-29) and a later one with 13 questions (SOC-13: the one employed in the analyses presented here), although a considerable number of modified versions of both have also been used. 13 Overall the measure has been deemed to be a ‘reliable, valid and cross-culturally applicable instrument’, 13 and has been shown to be significantly associated with a wide variety of outcomes, in particular: various measures of quality of life 14 15 and perceived health status; 16 mental health, 16 16a (eg depression, hopelessness, 13 17–20 anxiety, post-traumatic stress symptoms, 21 psychiatric disorders 22 and suicide 23 ); crime; 24 risk of tobacco use 25 and alcohol and drug problems. 26 27 Some reviewers have questioned its association with physical health, 17 citing considerably mixed evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Two versions of the SoC scale were created by Antonovsky, one with 29 questions (SOC-29) and a later one with 13 questions (SOC-13: the one employed in the analyses presented here), although a considerable number of modified versions of both have also been used. 13 Overall the measure has been deemed to be a ‘reliable, valid and cross-culturally applicable instrument’, 13 and has been shown to be significantly associated with a wide variety of outcomes, in particular: various measures of quality of life 14 15 and perceived health status; 16 mental health, 16 16a (eg depression, hopelessness, 13 17–20 anxiety, post-traumatic stress symptoms, 21 psychiatric disorders 22 and suicide 23 ); crime; 24 risk of tobacco use 25 and alcohol and drug problems. 26 27 Some reviewers have questioned its association with physical health, 17 citing considerably mixed evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Sense of Coherence has received considerable attention in the health care literature ( Langius-Eklof, Lidman & Wredling, 2009 ). For example, it has been explored in nursing interventions for cancer patients ( Delbar & Benor, 2001 ) and the treatment of young people at risk of developing mental disorders ( Ristkari et al, 2009 ). Delbar and Benor (2001) investigated whether the ability to cope depends on internal resources or can be increased through a structured nursing intervention–the Self-Care Approach.…”
Section: Resultsmentioning
confidence: 99%
“…Within context of academic stress, a sense of coherence also serves as a stress absorber (Modin, Östberg, Toivanen & Sundell, 2011). It is informative how Ristkari et al (2009) found that a lower sense of coherence is associated with antisocial behavior in male adolescent Finnish students. In other cultural contexts, a sense of coherence might be a suitable mediator of influential family factors in the appearance of behavioral problems.…”
Section: Theoretical Frameworkmentioning
confidence: 98%